Got here as soon as I could : discovering the way life should be - Smiley, Sarah (Down East Books, 2016)
GOT HERE AS SOON AS I COULD is a collection of syndicated columnist Sarah Smiley's most-loved columns about raising a family in Maine. In these 100 essays, readers will laugh, cry and nod their head "yes" as they remember a time when all of America was as simple and beautiful as it still is today in Vacationland